Transcription Factor USF1 Is Required for Maintenance of Germline Stem Cells in Male Mice - Faisal I.; Cisneros-Montalvo S.; Hamer G.; Tuominen M.; Laurila P.; Tumiati M.; Jauhiainen M.; Kotaja N.; Toppari J.; Mäkelä J-A.; Kauppi L. (Oxford University Press, 2025)
A prerequisite for lifelong sperm production is that spermatogonial stem cells (SSCs) balance self-renewal and differentiation, yet factors required for this balance remain largely undefined. Using mouse genetics, we now demonstrate that the ubiquitously expressed transcription factor upstream stimulatory factor (USF)1 is critical for the maintenance of SSCs. We show that USF1 is not only detected in Sertoli cells as previously reported, but also in SSCs. Usf1-deficient mice display progressive spermatogenic decline as a result of age-dependent loss of SSCs. According to our data, the germ cell defect in Usf1−/− mice cannot be attributed to impairment of Sertoli cell development, maturation, or function, but instead is likely due to an inability of SSCs to maintain a quiescent state. SSCs of Usf1−/− mice undergo continuous proliferation, which provides an explanation for their age-dependent depletion. The proliferation-coupled exhaustion of SSCs in turn results in progressive degeneration of the seminiferous epithelium, gradual decrease in sperm production, and testicular atrophy. We conclude that the general transcription factor USF1 is indispensable for the proper maintenance of mammalian spermatogenesis.